Adult intussusceptions: Clinical presentation, diagnosis and therapeutic management. (2017) - Maghrebi, H.; Makni, A.; Rhaiem, R.; Atri, S.; Ayadi, M.; Jrad, M.; Jouini, M.; Kacem, M.; Bensafta, Z.
Highlights: This is a rare entity. Its treatment still difficult because of controversy regarding the diagnosis and the optimal management. We tried to present our experience with 8 adult intussusceptions cases followed by a review of the literature in order to analyze the cause, clinical features, diagnosis, and management of this rare pathology. It was a retrospective study, But it is very interesting with clear results and excellent figures which may guide surgeons who encounter this problem. I am hoping that you have received everything as required and that the reviewing process finds the manuscript acceptable for publication in the journal. Please accept again dear professor our most humble greetings. Abstract: Background: Adult intussusception is a rare clinical entity. It is an uncommon cause of intestinal obstruction in adult. It often presents with nonspecific symptoms and preoperative diagnosis remains difficult. The purpose of this study was to determine the clinical entity and surgical approach of adult intussusception. Methods: We have conducted a retrospective descriptive study starting from 2006 until 2014. We reviewed data for all patients that had been admitted to our department for intestinal intussusception. Results: Eight consecutive patients were admitted to our department. The mean age was 48 years old (20–71). The sex ratio was 0, 6. The clinical presentation was acute in 5 cases. A computed tomography was performed in 6 cases. The diagnosis of gastrointestinal intussusception was made preoperatively in 100% of patients. All patients underwent surgery. An organic lesion was identified in 100% of the cases. In all cases, resection of the intussuscepted intestinal loop was done without intestinal reduction. All patients were well followed up and recurrences have been documented. Conclusion: In adults, intussusception is usually secondary to an organic cause. In the absence of signs of severity, etiologic diagnosis based on CT allows the diagnosis of the intussusception and sometimes can detect the causal lesion. Therapeutic sanction of intussusception is surgery and there is more emphasis towards resection without reduction.